A Proposed System Concept on Enhancing the Encryption and Decryption Method for Cloud Computing - Sakinah Ali Pitchay; Farida Hazwani Mohd Ridzuan; Madihah Mohd Saudi; Alhiagem, WAA (IEEE, 2024)
Indexed by WOS/SCOPUS